UNIX for OpenVMS users - Bourne, Philip E.; Holstein, Richard, 1950-; McMullen, Joseph, 1954- (Boston : Digital Press, 2003)
UNIX for OpenVMS Users, 3E, makes it easy to see what OpenVMS and UNIX have in common, and to transfer your knowledge and experience in OpenVMS over to the world of UNIX. Since most shops rely on more than one operating system, it is critical for system administrators and managers to understand the similarities and differences between platforms, so they can easily work in both environments while taking full advantage of the tools and applications available on each. This book offers OpenVMS professionals a concise source of information, so that they can quickly bring their expertise to bear on UNIX file management, e-mail, networking, and security. This new edition of the book is enhanced with updated references to VMS, incorporates suggestions made by readers of previous editions, and particularly, recognizes other UNIX implementations in addition to HP's Tru64. Includes extensive additions to the sections on VMS logical names, on the emacs editor, and on shell programming and Perl Describes the interfaces common to both operating systems, with appendices covering command and editor summaries Adds emphasis on Linux.
Fundamentals -- Getting started -- Introductory file management -- Editing -- Communicating with other users -- Devices, queues, and background processing -- File management revisited -- Programming -- Shell programming -- Administration -- Monitoring and utilizing system resources -- Networking.
Includes index.
Keywords: UNIX (Computer file); Operating systems (Computers).; OpenVMS; Open VMS (Computer file); Electronic books